Ba2M(C3N3O3)2 (M = Mg, Ca): potential UV birefringent materials with strengthened optical anisotropy originating from the (C3N3O3)3− group. Issue 47 (19th November 2018) - Li, Zhuang; Liang, Fei; Guo, Yangwu; Lin, Zheshuai; Yao, Jiyong; Zhang, Guochun; Yin, Wenlong; Wu, Yicheng; Chen, Chuangtian
Abstract : (C3 N3 O3 ) 3− is first proposed to be an excellent birefringent active group and the representative compounds Ba2 M(C3 N3 O3 )2 (M = Mg and Ca) are studied in detail. Abstract : Demands for UV birefringent materials are growing dramatically owing to the rapid development of ultraviolet technology. Here, a new family of UV birefringent materials, Ba2 Mg(C3 N3 O3 )2 (BMCY) and Ba2 Ca(C3 N3 O3 )2 (BCCY), have been successfully discovered. It is the first time that the excellent birefringent properties of cyanurates have been studied. These materials exhibit an extremely large birefringence (Δ n = 0.728–0.351 and 0.771–0.346 from 230 nm to 800 nm for BMCY and BCCY, respectively), much larger than that of the commercial UV birefringent crystal α-BaB2 O4 (α-BBO) (Δ n = 0.12@532 nm). Our study indicates that the impressive optical properties of BMCY and BCCY stem from the strengthened optical anisotropy of the planar (C3 N3 O3 ) 3− group compared with the isoelectronic (B3 O6 ) 3− group. Besides, its congruent-melting properties make it feasible to grow a bulk crystal by the Bridgman–Stockbarger technique. The extraordinary properties of BMCY and BCCY may shed light on a new path to explore birefringent materials for practical application.